A study of clinical profile of children with short stature - Angadi, Kumar; Ahmed, Mohammed Mukeeb; Bhimalli, Shivanand S; Patil, Sharanagouda (Indian Journal of Child Health, 2021)
Background: Short stature is one of the common concerns among the Indian children. However, community-based studies in Indian context are rare compared to studies performed in Western countries. Aim: Here, we aimed to study the clinical profile of children with short stature and the different causes of it. Methods: This study was a hospital-based prospective study that included 65 children ?18 years (female: 57%, male: 43%) who met the inclusion criteria. Detailed history, physical examination, anthropometry, laboratory tests, bone age, and chromosomal analysis were included for evaluation. Results: The most common age group affected was 11–15 years (40%) followed by 6–10 years (34%) and